2018
DOI: 10.1515/hukin-2017-0182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Kinematics and Muscle Activity Between Elite and Amateur Table Tennis Players During Topspin Loop Against Backspin Movements

Abstract: This study investigated differences of lower limb kinematics and muscle activity during table tennis topspin loop against backspin movements between elite players (EPs) and amateur players (APs). Ten EPs and ten APs performed crosscourt backhand loop movements against the backspin ball with maximal power. Vicon motion analysis and a MEGA ME6000 system was used to capture kinematics and surface EMG data. The motion was divided into two phases, including the backswing and swing. The joints’ flexion and extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
(15 reference statements)
1
32
0
1
Order By: Relevance
“…Comparative research in table tennis has most often concerned players of different levels, age, training experience, etc. [ 21 , 26 , 27 ] or comparison of the kinematics of different shots [ 28 , 29 ]. Gender differences in kinematics have been found in other sports, emphasizing the need to individualize and adapt training programs to the gender of athletes [ 15 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative research in table tennis has most often concerned players of different levels, age, training experience, etc. [ 21 , 26 , 27 ] or comparison of the kinematics of different shots [ 28 , 29 ]. Gender differences in kinematics have been found in other sports, emphasizing the need to individualize and adapt training programs to the gender of athletes [ 15 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to increase the training measures that shape exibility in the motor training process of these young players. Table tennis belongs to the group of sport disciplines where the level of coordination and speed skills, especially of the upper limbs, should be at the highest level [53][54][55][56]. This study showed that the table tennis players obtained the best results in the SHR test assessing the level of these abilities.…”
Section: Discussionmentioning
confidence: 65%
“…However, these differences may also be due to tactical requirements, especially in male table tennis. It is noticeable that in table tennis at the world elite level, topspin backhand is not only the first attack but also a stroke that directly yields a point [ 5 ]. Quantitative analyses show that men attack more often, use higher forces, and take more risk than women [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most often, researchers in the field of table tennis evaluate the topspin stroke, as it is considered the most commonly used one to score a point [ 3 , 4 , 5 , 6 ]. For example, authors dealing with the kinematics of topspin strokes compared athletes at different sports skill levels [ 5 , 7 , 8 , 9 ] and checked for differences between individual strokes [ 5 , 10 ]. Other authors searched for correlations between the kinematics of selected body segments and racket speed [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%